How infants categorize and individuate faces - Peykarjou, Stefanie (2018)
This thesis evaluates whether young infants can (1) individuate and (2) categorize faces and (3) which process(es) will be elicited under which circumstances. Using the EEG technique, I tested categorization and individuation of human faces in 9-month-old infants. In a rapid repetition event-related potential (rrERP) study, 80 different faces were presented for 1.5 s each while controlling for low-level stimulus characteristics such as luminance or contrast (study 1). 9-month-old infants showed a reduced N290 latency for repeated compared to novel identities, thus demonstrating the ability to individuate unfamiliar faces. Regarding broader infant face categorization abilities, study 2 employs the Fast Periodic Visual Stimulation (FPVS) technique and provides a full evaluation of infants’ ability to categorize faces according to species. This includes generalization across faces of one species and discrimination between faces of different species. 9-month-old infants categorized faces according to species, and this effect was reduced for inverted faces. As 9-month-old infants are able to individuate and to categorize unfamiliar faces, I developed a framework that may allow predicting how infants will categorize a face under given circumstances. In a first evaluation of this framework, I have provided evidence that under relatively difficult processing circumstances, infants will categorize but not individuate faces (study 3). In this rrERP study, houses, ape faces and human faces were presented to infants for 1 s each, and repetition effects were observed on the basic (“human”, “monkey”) and superordinate (“faces”) levels. No difference was found between repeated and novel faces. Together, these studies show that by nine months of age, infants are able to categorize and individuate faces, and task and stimulus characteristics may drive them to perceive faces differently. Future work should complement this knowledge by testing infants throughout the first year of life while controlling for factors that may determine whether infants will categorize or individuate faces.
Keywords: Hochschulschrift; Gesicht; Kategorisierung; Kind